PENGARUH PEMAHAMAN TEKNOLOGI INFORMASI, KARAKTERISTIK KUALITATIF LAPORAN KEUANGAN, UKURAN USAHA, DAN SOSIALISASI TERHADAP PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) (Studi kasus UMKM di Kecamatan Ngargoyoso) - Anang Hari Wicaksono; Ifah Lathifah (ADVANCE, 2018)
The purpose of this study is to investigate the effect of understanding information technology, characteristics of financial statements, company size and socialization on the implementation of financial accounting standards of entities without public responbility (IFRSs,) in SMEs in the district of Ngargoyoso, district of Karanganyar. This study uses regression data analysis techniques using the SPSS program. Collection is done by observation and questionnaire. The population of this study is all MSMEs in the sub-district Ngargoyoso and the sample used in this study is 30 respondents (MSMEs). The results of hypothesis tests showed that insight into information technology has a positive effect on the application of IFRS. The qualitative features of financial statements have a positive effect on the application of IFRSs,. Business measures have a negative effect on the application of IFRSs,. Socialization does not affect the implementation of IFRSs.Keywords: Understanding information technology, qualitative characteristics of financial statements, company size, socialization, implementation of IFRSs, MSME